The Role of Interpersonal Communication in Maximize the Use of QRIS in The Street Vendor Environment of UIN Raden Intan Lampung - Meiranti, Mike; Choiriyati, Sri; Jaya Wijaya (Jogjakarta Communication Conference (JCC), 2025)
QRIS is a digital payment method that makes it easy for users to carry out buying and selling transactions. Currently, using QRIS has become a transaction style that is popular, especially among young people. However, there are still many business actors who have not utilized RIS in the transaction process. With this background, this research aims to analyze and provide solutions for maximizing QRIS using an interpersonal communication approach and it is hoped that QRIS as a digital payment system will be able to provide easy transactions for traders and consumers, thereby potentially increasing sales volume. By using descriptive qualitative methods, researchers will examine the extent to which interpersonal communication is effective in encouraging the use of QRIS by street vendors and the research results are expected to show that good interpersonal communication such as direct education, demonstration of use, and persuasive approaches play an important role in increasing traders' trust and interest in using QRIS optimally. so that in the end optimal use of QRIS has a positive impact on increasing sales turnover.